2022
DOI: 10.3389/fpls.2022.951097
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA-based plant protection against diseases

Abstract: Plant diseases cause significant decreases in yield and quality of crops and consequently pose a very substantial threat to food security. In the continuous search for environmentally friendly crop protection, exploitation of RNA interferance machinery is showing promising results. It is well established that small RNAs (sRNAs) including microRNA (miRNA) and small interfering RNA (siRNA) are involved in the regulation of gene expression via both transcriptional and post-transcriptional RNA silencing. sRNAs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 136 publications
0
8
0
Order By: Relevance
“…Likewise, the AGO and DCL genes got triggered to downregulate by the dsRNA machinery and protect from Fg infection. , Besides this, the β2Tub gene of the F. asiaticum fungus can also encounter antifungal properties by RNAi spray on barley crops . Another fungal pathogen, Sclerotinia sclerotiorum (white mold), also affects barley crops, which can be prevented using SIGS …”
Section: Spray Induced Gene Silencingmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, the AGO and DCL genes got triggered to downregulate by the dsRNA machinery and protect from Fg infection. , Besides this, the β2Tub gene of the F. asiaticum fungus can also encounter antifungal properties by RNAi spray on barley crops . Another fungal pathogen, Sclerotinia sclerotiorum (white mold), also affects barley crops, which can be prevented using SIGS …”
Section: Spray Induced Gene Silencingmentioning
confidence: 99%
“…Additionally, the downy mildew pathogen ( Hyaloperonospora arabidopsidis ) attacking A. thaliana can also be killed using this very RNAi approach by suppressing the cellulose synthase corresponding gene. , A few more examples of pathogens that infect thale cress plants are Macrophomina phaseolina , F. graminearum , and Verticillium dhaliae . Rapeseed ( Brassica napus ) is an example of a plant falling under the Brassicaceae family, which also gets infected by B. cinerea and S. sclerotiorum , respectively, that can be regulated by SIGS …”
Section: Spray Induced Gene Silencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusarium graminearum development in barley leaves was suppressed by spraying dsRNA to target the fungal cytochrome P450, establishing the feasibility of spray-induced gene silencing (SIGS) [110]. Moreover, the potential non-transgenic, spray-based exogenous dsRNA or sRNA (SIGS) application has been widely used to decrease disease in crop plants [111][112][113][114].…”
Section: Spray-induced Gene Silencingmentioning
confidence: 99%
“…Studies conducted over the last 10 years have shown that miRNAs induced by pathogens can be effective regulators of plant resistance (R) genes encoding diverse proteins, including the following: NBS-LRR proteins; pathogenesis-related proteins; proteins associated with amino acid metabolism, replication, transport, and chelation of reactive oxygen species; cysteine-rich receptor-like protein kinases; ABC transporters; and other proteins related to plant immune responses [17,21,[24][25][26][27][28]. Many R genes expressed speci cally in response to rusts have recently been identi ed in wheat and rye [29,30].…”
Section: Introductionmentioning
confidence: 99%